Prospects of third-generation femtosecond laser technology in biological spectromicroscopy - Fattahi, Hanieh; Fattahi, Zohreh; Ghorbani, Asghar (Journal of Optics, 2018)
The next generation of biological imaging modalities will be a movement towards super-resolution, label-free approaches to realize subcellular images in a nonperturbative, non-invasive manner and towards new detection metrologies to reach a higher sensitivity and dynamic range. In this paper, we discuss how the third generation femtosecond laser technology in combination with the already existing concepts in time-resolved spectroscopy could fulfill the requirements of these exciting prospects. The expected enhanced specificity and sensitivity of the envisioned super-resolution microscope could lead us to a better understanding of the inter- and intra-cellular molecular transport and DNA-protein interaction.
CRIS-Team Scopus Importer:2023-04-20
Keywords: artificial intillegence; cognitive genomics; fieldresolved metrology; label-free microscopy; super-resolution microscopy; third-generation femtosecond laser technology; Yb:YAG oscillators